Human GABRG2 generalized epilepsy: Increased somatosensory and striatothalamic connectivity. (August 2019) - Pedersen, Mangor; Kowalczyk, Magdalena; Omidvarnia, Amir; Perucca, Piero; Gooley, Samuel; Petrou, Steven; Scheffer, Ingrid E.; Berkovic, Samuel F.; Jackson, Graeme D.
Abstract : Objective: To map functional MRI (fMRI) connectivity within and between the somatosensory cortex, putamen, and ventral thalamus in individuals from a family with a GABAergic deficit segregating with febrile seizures and genetic generalized epilepsy. Methods: We studied 5 adults from a family with early-onset absence epilepsy and/or febrile seizures and a GABAA receptor subunit gamma2 pathogenic variant ( GABRG2[R43Q] ) vs 5 age-matched controls. We infer differences between participants with the GABRG2 pathogenic variant and controls in resting-state fMRI connectivity within and between the somatosensory cortex, putamen, and ventral thalamus. Results: We observed increased fMRI connectivity within the somatosensory cortex and between the putamen and ventral thalamus in all individuals with the GABRG2 pathogenic variant compared with controls. Post hoc analysis showed less pronounced changes in fMRI connectivity within and between the primary visual cortex and precuneus. Conclusions: Although our sample size was small, this preliminary study suggests that individuals with a GABRG2 pathogenic variant, raising risk of febrile seizures and generalized epilepsy, display underlying increased functional connectivity both within the somatosensory cortex and in striatothalamic networks. This human network model aligns with rodent research and should be further validated in larger cohorts, including other individuals with generalized epilepsy with and without known GABA pathogenic variants.